Problem-Based Learning-Based Ipa Practicum Module To Improve Problem-Solving Ability - Endang Wahyudiana; Julius Sagita; Vina Iasha; Ari Setiantini; Ari Setiarini (Universitas PGRI Adi Buana Surabaya, 2021)
This study aims to determine the characteristics of Problem Based Learning-based science modules to improve problem-solving skills and to determine the feasibility of Problem Based Learning-based science modules. The method used in this study is the Research and Development proposed by Dick and Carey. Module development is assessed based on the feasibility of materials, learning tools, media, and language by 3 lecturers, 1 language expert, and 1 teacher. Data collection ability to solve problems using tests. The development stage of the Problem Based Learning-based science module to improve problem-solving skills in human and environmental materials begins with a needs analysis, the design stage is in the form of drafting the module draft, the develop stage is in the form of validating the module draft, after being valid, a trial is carried out. The modules developed have a very good quality category so that they are suitable for use in science learning. Furthermore, there is an increase in the average problem-solving ability during learning using a Problem Based Learning-based science module to improve problem-solving skills as indicated by the results of the pre-test and post-test.